2001
DOI: 10.1002/jms.148
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer via strained transition states in the elimination of alcohols from MH+ ions of stereoisomeric diethers and hydroxy esters upon chemical ionization and collision‐induced dissociation

Abstract: The isobutane chemical ionization (CI) mass spectra of cis-and trans-1,4-di(alkoxymethyl)cyclohexanes, with a tertiary alkoxy group ROH and a primary group R OH, are identical, and they exhibit exclusive elimination of the alcohol ROH originating from the tertiary alkoxyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Mass spectrometry is a powerful tool for studying the kinetics and mechanisms of organic reactions in the gas phase [13][14][15][16] and in particular of ion-molecule reactions. [17] Data from such studies deepened the understanding of the reaction chemistry of a wide range of reactive organic ions.…”
mentioning
confidence: 99%
“…Mass spectrometry is a powerful tool for studying the kinetics and mechanisms of organic reactions in the gas phase [13][14][15][16] and in particular of ion-molecule reactions. [17] Data from such studies deepened the understanding of the reaction chemistry of a wide range of reactive organic ions.…”
mentioning
confidence: 99%
“…However, the chemical environment such as solvent effect can change the preferred site of protonation [6,7]. It is also interesting that a molecule can be protonated at energetically less favored position when different ionization methods are used, reflecting a kinetic influence over the protonation site [8][9][10][11][12][13][14]. In the case of aniline, it has no objection that the amino group is the protonation site in aqueous solution because of its good stability from solvation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that aryls can be protonated at the phenyl ring or at the substituent, depending on the nature of the substituent. It has been shown, however, that under CI conditions protonation can be kinetically controlled, and thus the protonation site(s) could vary according to the experimental conditions 1, 4, 6–9. In a recent study, Harrison and Tu showed that fast atom bombardment ionization of N ‐alkylaniline derivatives leads to the formation of N ‐protonated species, whereas protonation in the gas phase leads to substantial formation of the ring protonated tautomer.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic effect in protonation can also be manifested in spontaneous dissociative processes. For example, it was found that trans ‐1,4‐cyclohexyl hydroxy‐esters undergo extensive water elimination under i‐Bu‐CI conditions, although the two basic groups cannot interact 8. This points to efficient interaction between the protonation reagent and the hydroxy group, which leads to the loss of water, although the PA of the alcohol group is lower than that of the ester group or isobutene 8…”
Section: Introductionmentioning
confidence: 99%